Sociodemographic determinants and mortality of premature newborns in a medium and low-income population in Colombia, 2017-2019 - Javier Torres-Muñoz; Daniel Alberto Cedeño; Jennifer Murillo; Sofía Torres-Figueroa; Julián Torres-Figueroa (Biomédica: revista del Instituto Nacional de Salud, 2023)
Introduction. The birth of premature babies is a public health problem with a high impact on infant morbidity and mortality. About 40% of mortality in children under five years occurs in the first month of life. Objective. To identify the association between maternal sociodemographic factors, premature birth, and mortality in newborns under 37 weeks in Santiago de Cali, 2017-2019. Materials and methods. We conducted a descriptive, cross-sectional study. We evaluated the records of Cali’s Municipal Public Health Office. We calculated the crude and adjusted odd ratios and confidence intervals (95%) using the logistic regression model, data processing in Stata 16, and georeferencing the cases in the QGIS software. Results. From 2017 to 2019, premature babies in Cali corresponded to 11% of births. Poor prenatal care increased 3.13 times the risk of being born before 32 weeks (adjusted OR = 3.13; 95% CI = 2.75 - 3.56) and 1.27 times among mothers from outside the city (adjusted OR = 1.27; 95% CI = 1.15-1.41). Mortality was 4.29 per 1,000 live births. The mortality risk in newborns weighing less than 1,000 g increased 3.42 times (OR = 3.42; 95% CI = 2.85-4.12), delivery by cesarean section in 1.46 (OR = 1.46; CI 95% = 1.14-1.87) and an Apgar score – five minutes after birth– lower than seven in 1.55 times (OR = 1.55; CI 95% = 1.23-1.96). Conclusions. We found that less than three prenatal controls, mothers living outside Cali, afro-ethnicity, and cesarean birth were associated with prematurity of less than 32 weeks. We obtained higher mortality in newborns weighing less than 1,000 g.